Electrocatalytic hydrogenation and depolymerization pathways for lignin valorization: toward mild synthesis of chemicals and fuels from biomass - Wijaya, Yanuar Philip; Smith, Kevin J.; Kim, Chang Soo; Gyenge, Elod L. (Royal Society of Chemistry, 2020)
Lignin is a prospective resource for renewable commodity organic chemicals and fuels. In the scheme of a sustainable biorefinery, lignin valorization is essential for enhancing the economic feasibility of the overall biomass transformation processes. Electrocatalysis and electrochemical processes are expected to play a major role in biomass valorization due to the possibility of using renewable electricity sources for in situ production of 'green' H-2 and other reagents that are necessary for biomass conversion. Recent advances in the electrocatalytic hydrogenation and hydrogenolysis of lignin derivatives, including oxygenated aromatic compounds, suggest promising pathways for the synthesis of industrially relevant chemicals, such as ketone-alcohol (KA) oil, the mixture of cyclohexanone and cyclohexanol for the production of Nylon polymers. This review presents the prospect of electrocatalytic reduction approaches for a mild synthesis of lignin-based chemicals with emphasis on the potential applications of high current density electrolysis. Feasible electrocatalytic oxidation strategies for lignin depolymerization are also summarized, highlighting the fundamental differences between the electrochemical reductive and oxidative routes. Finally, challenges and opportunities for future development of the electrocatalytic pathways for lignin valorization are discussed.